Effects of five extraction methods on the physicochemical properties, antioxidant, and α-glucosidase inhibitory activities of polysaccharides from wild jujube flesh - Shuhui Yuan; Guolong Li; Jinao Duan; Zhishu Tang; Zhongxing Song; Hongbo Liu; Xinbo Shi (Applied Food Research)
Wild jujube, known as “green gem”, is rich in polysaccharides. This study evaluated the effects of various extraction techniques, including hot water extraction, alkali extraction, acid extraction, and enzyme extraction, on the physicochemical properties, antioxidant properties, and α-glucosidase inhibitory activities of polysaccharides extracted from wild jujube flesh (WJFP). The results showed significant variations in polysaccharide yield and characteristics among five WJFPs. The total polysaccharide content ranged from 47.31% to 67.60%, while the protein content ranged from 1.29% to 1.87%. Despite similar monosaccharide compositions (arabinose, xylose, galactose, and glucuronic acid), their proportions showed notable differences. Infrared spectroscopy indicated that the samples contained similar typical polysaccharide peaks, while nuclear magnetic resonance spectroscopy revealed consistent glycosyl residue types across all WJFPs. In terms of bioactivity, WJFP-Ac exhibited hydroxyl radical scavenging, while WJFP-HA and WJFP-E demonstrated effective α-glucosidase inhibition. WJFP-HA also demonstrated strong antioxidant abilities, including DPPH scavenging and total antioxidant characteristics. The findings of this study highlighted how molecular weight and monosaccharide composition influenced the bioactivity of WJFP, providing a foundation for optimizing the extraction and utilization of WJFPs in various applications.